Camptodactyly and DiGeorge syndrome: A rare hand anomaly. (June 2021) - Hurley, C.M.; McHugh, N.; Carr, S.; Kelly, J.L.
Summary: The most common deletion syndrome is 22q11.2 and it effects an estimated 1 in 3000 live births. Major features of this multisystem condition include congenital abnormalities, developmental delay, learning difficulties, immunodeficiency, endocrine anomalies and an array of psychiatric disorders. However, variability in phenotype and severity may cause the diagnosis to be overlooked. Early clinical recognition and treatment of DiGeorge syndrome has been shown to increase early life survival, decrease complications and enhance overall quality of life. Skeletal anomalies are infrequently described in 22q11.2 but a subset of patients exhibit upper and lower limb deformities. We present the case of a 5 year-old girl with bilateral fifth digit camptodactyly caused by a fibrous band, and the surgical management of this condition. The current report adds to the body of evidence that camptodactyly is a rare clinical feature of 22q11.2 deletion syndrome, and may serve as a diagnostic aid in these patients.